The Effect of Financial Literacy, Income and Self Control on Financial Behavior Generation Z (Study on Generation Z Financial Behavior in Bekasi Regency) - Gea Trivani; Erin Soleha (Universitas Negeri Semarang, 2023)
Financial behavior is an important thing to pay attention to, with good financial behavior a person will beable to meet his needs both from the short and long term. The purpose of this study was to determine and analyze the effect of financial literacy, income and self-control on thelimited financial behavior of generation Z. The population of this study is generation Z in Bekasi Regency. This studyused quantitative research with data collection techniques using questionnaires. The sampling technique in this study is by using urposive sampling techniques, so that the number of samples inthis study was 100 respondents. And the technique of data analysis inthis research is using Structural Equation Modelling (SEM) withthe help of SmartPLS version 4.0 for windows. The results of this study found that financial liability variables have a negative and insignificant effect on financial behavior in generation Z in Bekasi Regency, income variables have a positive and significant effect on financial behavior in generation Z in Bekasi regency.ini show that income can increase financial behavior in generation Z in Bekasi regency, where the higher a person's income level, the more Be careful about using money. In managing finances, generation Z must remember that both large and small income they have from working and investing, they still have to manage their finances well. Then the variable of self-control has a positive and significant effect on financial behavior. This means that the higher the self-control, the better the financial behavior.